2012
DOI: 10.1002/jcb.24025
|View full text |Cite
|
Sign up to set email alerts
|

IL‐4 induces proliferation in prostate cancer PC3 cells under nutrient‐depletion stress through the activation of the JNK‐pathway and survivin up‐regulation

Abstract: Interleukin (IL)-4 plays a critical role in the regulation of immune responses and has been detected at high levels in the tumor microenvironment of cancer patients where it correlates with the grade of malignancy. The direct effect of IL-4 on cancer cells has been associated with increased cell survival; however, its role in cancer cell proliferation and related mechanisms is still unclear. Here it was shown that in a nutrient-depleted environment, IL-4 induces proliferation in prostate cancer PC3 cells. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 46 publications
(66 reference statements)
2
71
1
Order By: Relevance
“…Large amounts of T H 2 cytokines are observed in the tumor microenvironment and peripheral blood of patients with prostate, bladder and breast cancers [37][38][39] . IL-4 can directly induce the proliferation of colon, breast, head and neck, ovarian and prostate cancer cells in vitro [40][41][42] and can also activate myeloid cell-derived suppressor cells 43 or type 2 tumor-associated macrophages 44 and inhibit T H 1 polarization. We have now provided evidence that in mouse cancer models in which T H 2 cells accumulated in wild-type mice, deficiency in NLRP3 blunted the accumulation of T H 2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of T H 2 cytokines are observed in the tumor microenvironment and peripheral blood of patients with prostate, bladder and breast cancers [37][38][39] . IL-4 can directly induce the proliferation of colon, breast, head and neck, ovarian and prostate cancer cells in vitro [40][41][42] and can also activate myeloid cell-derived suppressor cells 43 or type 2 tumor-associated macrophages 44 and inhibit T H 1 polarization. We have now provided evidence that in mouse cancer models in which T H 2 cells accumulated in wild-type mice, deficiency in NLRP3 blunted the accumulation of T H 2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Haeng Park et al (2014) also confirmed that the anti-atherosclerotic effects of Polygonum aviculare L. ethanol extract in ApoE -/-mice are mediated via the MAPK pathway. Furthermore, high levels of IL-4 in the tumor microenvironment were observed, which could activate MAPKs, including ERK, p38, and JNK (Roca et al, 2012). Jiménez-Garcia et al (2015) demonstrated that p38 MAPK could play a pivotal role in IL-4-induced alternative activation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The IL4/IL4R interaction has been shown to enhance the proliferation and survival of breast cancer cells in vitro [6,7], and the survival of other epithelial cancer cell types in vivo [4]. Still, there is no data regarding the influence of IL4R expression on the proliferation and survival of breast cancer cells in vivo , or on metastatic tumor growth in general.…”
Section: Introductionmentioning
confidence: 99%